The Effect of Acupressure And Lavender Aromatherapy Techniques on Complaints of Low Back Pain In Third Trimester Pregnant Women In Public Health Of Trauma Center Samarinda - Fara Imelda Theresia; Dwi Hendriani; Syamsiah Syamsiah; Eliza Anggraini (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Discomfort in pregnancy that is felt by pregnant women is influenced by the body's metabolic system and the musculosceletal system. Changes that occur during pregnancy are often a complaint for pregnant women including nausea, vomiting, constipation, urinary disorders and back pain. Various efforts to overcome pain can be done through activities without drug administration including acupressure and aromatherapy.The purpose of this study was to determine the effect of acupressure and lavender aromatherapy techniques on complaints of low back pain in third trimester pregnant women. The methods in this study is quasy experiment with two group pre-test and post test design. The population is pregnant women who make Ante Natal Care at the Trauma Center Health Center in Samarinda City, with a gestational age of more than 28 weeks who experience back pain. 18 pregnant women conducted acupressure that combine with lavender aromatherapy (intervention group), and 18 pregnant women for acupressure as control group. The result of this study indicate there is significant differences at pain scale between 2 groups after intervention (p-value = 0,0023) with a = 0,05. It means an effect of giving combination of prenatal yoga with lavender aromatherapy for pregnant woman’s back pain.